Factor Affecting the Perception of Traumatic Childbirth: A Cross-Sectional Study in Pregnant Women Women - Kübra Karabulut; Sercan Mansuroğlu; Ayşegül Unutkan (Atatürk University, 2024)
Objective: In order to experience all the processes of pregnancy and childbirth in a healthy way, it is necessary that the perception of traumatic birth is not high and the affecting factors should be known. This study was conducted to evaluate the factors affecting pregnant women's perception of traumatic childbirth. Methods: A cross-sectional and descriptive study consisted with 305 pregnant women, who was in the last trimester of their pregnancy. Data collected face-to-face using the Perception of Traumatic Childbirth Scale and the socio-demographic, obstetric and birth-related information form. Results: All of the pregnant women included in the study were married and their mean age was 28.04±5.20 years. The mean score of the pregnant women from the scale was 56.46±1.56 (Min-Max=0-120). Statistical significance was found between the score obtained from the scale and income status, the total number of miscarriages/mortal deliveries, mode of termination of the last delivery, fear experienced at the last delivery and anxiety experienced at the last delivery.Conclusion: A thorough understanding of the factors that influence and/or increase the perception of traumatic childbirth could contribute to the development of birth services as well as the protection and promotion of women's and pregnant's mental well-being.